1976
DOI: 10.1063/1.1134491
|View full text |Cite
|
Sign up to set email alerts
|

Cryostat for generating pressures to 100 kilobar and temperatures to 0.03 K

Abstract: An apparatus is described which allows studies to pressures of 100 kilobar and to temperatures of 0.03 K. A low temperature hydraulic press is incorporated with a dilution refrigerator to permit the continuous variation in pressure while at low temperature; thus, the entire pressure study of a material can be accomplished in one low temperature run. The sample is sensed magnetically using a SQUID magnetometer to detect changes in its magnetic moment. Operation of the system is described for measurements of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Nevertheless many coil arrangements in DACs exist (Eremets, 1996). Pressures up to 15 GPa (Cornelius et al, 1996) and temperatures of 30mK have been reported (Webb et al, 1976). Neutron diffraction is very sensitive to the magnetic order (Goncharenko & Mirebeau, 1998), but the determination of the magnetic moment variations remains limited in precision (Link et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless many coil arrangements in DACs exist (Eremets, 1996). Pressures up to 15 GPa (Cornelius et al, 1996) and temperatures of 30mK have been reported (Webb et al, 1976). Neutron diffraction is very sensitive to the magnetic order (Goncharenko & Mirebeau, 1998), but the determination of the magnetic moment variations remains limited in precision (Link et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is that the pressure-induced changes in the lattice vibrations dominate over those in the electronic system, leading to a decrease in T c as the lattice stiffens under pressure. In such simple-metal systems it is an interesting physics question to explore the manner in which T c approaches 0 K as the pressure in increased; pioneering studies in this direction were carried out in the 1970's by Gubser and Webb [3] on superconducting Al by combining diamond-anvil cell, dilution refrigeration, and SQUID detection technology [4]. Such high-pressure investigations at mK and sub-mK temperatures, however, are extraordinarily difficult and require that the materials studied be highly purified to contain only trace concentrations of magnetic impurities.…”
Section: Introductionmentioning
confidence: 99%
“…У пере-ходных металлов повышение давления может либо повышать, либо пони-жать температуру сверхпро-водящего перехода, в случае непереходных металлов тем-пература перехода, по-види-мому, понижается с повыше-нием давления. В Военно-морской исследовательской лаборатории разработан ап-парат высокого давления с алмазными наковальнями,, позволяющий работать при низких температурах до 0,03°К при давлении до 100 кбар 11 . Образец помещается внутри прокладки из бериллиевой бронзы, а маг-нитный момент, возникающий из-за эффекта Мейсснера, измеряется с по-мощью магнитометра со сверхпроводящим квантовым интерференционным устройством.…”
Section: электрические свойстваunclassified